From the Editor - de la Peña, Wystan (Linguae et Litterae; 2008, 2010)
As the University of the Philippines marks its centennial, the Linguae et Litterae begins a new chapter. With this issue—featuring essays and translations in five languages—it now joins the ranks of peer-reviewed journals. This issue features historical documentation on the Department of European Languages (DEL)—fittingly so, with the university’s centennial, and the DEL centennial in two years’ time—and critical essays on Fil-hispanic literature. This latter aspect is a significant one, given the fact that the University of the Philippines, through the DEL, is the only university offering graduate degrees in Hispanic studies. The critical effort towards preserving one of the country’s literatures already marginalized by the language barrier thus falls on the shoulders of the university, through the DEL.